Triangulations: Musicalized drama, folklore and identity construction in Nakae Yūji's A Midsummer's Okinawan Dream. (24th March 2017) - Johnson, Henry
Abstract : Japanese film director Nakae Yūji's 2009 feature film A Midsummer's Okinawan Dream: Majirū of the Triangular Mountain (Manatsu no yo no Yume: Sankaku Yama no Majirū) is rooted in the culture, folklore and soundscapes of the Okinawan islands and uses imagery, sound, music and narrative to explore many traits that epitomize Okinawa's distinct cultural identity in modern-day Japan. This article discusses the film from two main perspectives: (1) how different musical styles operate as distinct elements of the soundtrack (drawing on and embellishing their source contexts and traditions); and (2) how music functions in particular scenes and across the narrative in general. The article identifies the manner in which the film embraces local, national and global musical sources to provide a cultural soundscape that helps show some of the complexities of local identity construction in an era where regional identities are often contrasted against broader national and global influences.